Achieving Stable Cycling of LiCoO2 at 4.6 V by Multilayer Surface Modification. (13th May 2020) - Cheng, Tao; Ma, Zhongtao; Qian, Ruicheng; Wang, Yeting; Cheng, Qin; Lyu, Yingchun; Nie, Anmin; Guo, Bingkun
Abstract: LiCoO2, which was first proposed as a cathode in 1980 by Prof. John B. Goodenough, is still one of the most popular commercial cathodes for lithium‐ion batteries. Tremendous efforts have been invested in increasing the capacity of LiCoO2 by charging to high voltage. However, a series of issues, such as structural instability and dramatic side reactions with electrolytes, can emerge as cut‐off voltage above 4.5 V (vs Li/Li + ). Here, a surface modification strategy with a multilayer structure is provided, involving a Zn‐rich surface coating layer, rock‐salt phase buffer layer and surface gradient Al doping layer, to overcome the detrimental issues and achieve stable cycling of LiCoO2 at 4.6 V. The complete coating of the modification layer restrains the interfacial side reactions with electrolyte and inhibits the impedance growth. The phenomenon of quasi‐epitaxial growth demonstrates that the multilayer structure significantly reduces the lattice mismatch between host LiCoO2 and surface coating layer and enhances the stability of the Zn‐rich outside layer, which promote the long‐term effectiveness of the modification. Furthermore, the disordered rock‐salt phase layer and Al surface doping also enhance the structural stability. All of these synergistically lead to the stable cycling of LiCoO2 at 4.6 V with a capacity retention of 65.7% after 500 cycles. Abstract : A multilayer structure on the surface of LiCoO2, composed by a Zn‐rich layer with a wurtzite phase, a rock‐salt phase buffer layer, and a surface gradient Al doping layer, is formed to resolve the deleterious issues when operating at 4.6 V. The quasi‐epitaxial Zn‐rich layer can work well during long‐term cycling. The rock‐salt layer and gradient Al doping layer improve the structural stability.